Implementation of Gestalt Counseling on Self-Disclosure in Group Counseling for Victims of Sexual Harassment - Robbi Asri; Neviyarni S; Netrawati; Rendy Amora (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article discusses the implementation of existential counseling in overcoming trauma in victims of sexual harassment, where we know that currently cases of sexual harassment in the last few years have increased and have had a very painful impact on victims and have left a condition of prolonged trauma. The trauma resulting from sexual harassment results in psychological impacts. Victims of sexual violence and harassment will experience deep trauma and physical impacts. Violence and sexual abuse of children are the main factors in the transmission of Sexually Transmitted Diseases (STDs), and have social impacts. Victims of sexual violence and harassment are often ostracized in social life, something that should be avoided because victims definitely need motivation and moral support to get back on their feet in life. These problems that occur need to be resolved so that they do not interfere with daily life. This article also discusses existential counseling as a strategy for overcoming trauma in victims of bullying including the concept of trauma, sexual harassment, signs of sexual harassment, the impact of sexual harassment, basic theories and principles of views on human nature, the existential counseling process, the goals of existential counseling, the function and role of the counselor, the role of the client in the counseling relationship, the relationship between the counselor and the client in the counseling process, counseling procedures and techniques as well as the implementation of existential counseling in overcoming the trauma of victims of sexual harassment. The method used is a literature review with critical analysis of research being conducted on a specific topic.